SINTESIS DAN UJI TOKSISITAS SENYAWA 2’,4’-DIKLORO-4-METOKSIKALKON - Mega Cahayani; Agung Rahmadani; Dewi Rahmawati; Rolan Rusli (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Chalcone is one of secondary metabolites included into the class of flavonoid. Chalcone can be obtained from isolation plant and have various biological activities. Chalcones are known as the key intermediate in the synthesis of various biologically important heterocyclic compounds. The aims of these research was to syntheses 2’,4’-dichloro-4-methoxychalcone. by Claisen–Schmidt condensation. These compound was characterized by 1H-NMR, 13C-NMR and mass spectroscopy. LC50 value of these compound was 864,97 ppm